Evaluation of tears oxidative stress markers in Malay age-related macular degeneration patients - Ni, Koh Yi (2018)
Introduction: Oxidative stress has been postulated to play a role in the pathogenesis of age-related macular degeneration (ARMD). The increased oxidative stress and impaired antioxidant defenses are some contributory factor to the initiation and progression of ARMD. Thus, detection of oxidative stress level in ocular tissue may perhaps provide insight into a role of oxidative stress in pathogenesis of ARMD. Objective: Our objective was to compare the oxidative stress level, namely glutathione peroxidase, catalase, and malondialdehyde in tears, between Malay ARMD patients and controls. This study also to compare the mean level of oxidative stress markers between different severities of ARMD. Methods: A cross sectional study was conducted between September 2015 and November 2017 involving Malay patients with confirmed diagnosis ARMD and controls, attending eye clinic of two tertiary hospitals in Malaysia; Hospital Universiti Sains Malaysia and Hospital Raja Permaisuri Bainun. Tear samples collected by using Schirmer paper. Laboratory analysis was performed to test on glutathione peroxidase, catalase and malondialdehyde level of tears using commercially available oxidative stress markers kits. Statistical analysis was done using Statistical Package for the Social Science (SPSS Inc Version 20). Results: A total of 136 ARMD patients (early ARMD: 68 patients, late ARMD: 68 patients) and 68 controls were included into the study. Mean catalase level and glutathione peroxidase level were significantly lower in ARMD patients [1348.97 (109.11) μM and 453.87 (41.96) U/L respectively] as compared to controls [1453.38 (38.87) μM and 502.28 (34.29) U/L respectively] before (P<0.001 and P<0.001) and after adjusted for age (P=0.001 and P<0.001). There was no significant difference for malondialdehyde level between ARMD and controls. Catalase level was significantly lower in late ARMD group as compared to early ARMD group [1309.29 (112.47) μM vs 1388.06 (100.31) μM, P=0.044] and also after adjusted for age (P=0.029). Among the subtypes of neovascular late ARMD, catalase level was significantly higher in idiopathic polypoidal choroidal vasculopathy (IPCV) group compared to neovascular ARMD [1393.24 (53.12) μM vs 1267.27 (128.21) μM, P=0.031] and also after adjusted for age (P=0.027). Conclusion: This study showed that insufficient antioxidant capacity (lower catalase and glutathione peroxidase level) may play an important role in pathogenesis of ARMD. Catalase level was significantly related to severity of ARMD and IPCV among the subtypes of neovascular late ARMD after adjusted for age.